2019
DOI: 10.3389/fmicb.2019.00788
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic and Phenotypic Characterization of Clinical Escherichia coli Sequence Type 405 Carrying IncN2 Plasmid Harboring blaNDM-1

Abstract: We report a bla NDM -carrying ST405 Escherichia coli recovered from the abdominal fluid of a patient in Shandong, China. This strain belonged to the high-risk phylogenetic group D and carried the virulence genes, papG II, papG III, papC , and iroN. In addition to bla NDM-1 , this isolate carried the quinolone resistance gene acc(6′)-Ib and extended-spectrum β-lactamase (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 33 publications
2
12
0
Order By: Relevance
“…BLASTp search using the amino acid sequence of RepA SGI1 showed 10–60% similarities to IncN RepA proteins, depending on the subgroup of IncN family. RepA SGI1 significantly differed (<10% identity) from the RepA proteins of IncN1 plasmids ( 43 ), and appeared much more similar (50–60% identity) to those of IncN2 group ( 42 , 41 ) and pN- Cit classified as IncN3 ( 44 ). The phylogenetic reconstruction based on the RepA proteins did not support the separation of IncN2 and IncN3 groups, while IncN1 was clearly distinct from them and possibly forms a different family.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…BLASTp search using the amino acid sequence of RepA SGI1 showed 10–60% similarities to IncN RepA proteins, depending on the subgroup of IncN family. RepA SGI1 significantly differed (<10% identity) from the RepA proteins of IncN1 plasmids ( 43 ), and appeared much more similar (50–60% identity) to those of IncN2 group ( 42 , 41 ) and pN- Cit classified as IncN3 ( 44 ). The phylogenetic reconstruction based on the RepA proteins did not support the separation of IncN2 and IncN3 groups, while IncN1 was clearly distinct from them and possibly forms a different family.…”
Section: Resultsmentioning
confidence: 93%
“…The repA transcript was previously reported to be one of the less abundant mRNAs synthesized from a chromosomally integrated island ( 24 ) and it was not clear whether this gene is functional at all. Pfam search indicated that the putative RepA protein of SGI1 belongs to the RepA_C-domain-containing proteins and further comparative analysis suggested that it is related to the replication initiator proteins of the broad host range plasmids of IncN family ( 42 ) ( Supplementary Figure S1 ). BLASTp search using the amino acid sequence of RepA SGI1 showed 10–60% similarities to IncN RepA proteins, depending on the subgroup of IncN family.…”
Section: Resultsmentioning
confidence: 99%
“…One additional difference between the two plasmids was the presence of Tn 5403 transposon in p47733_OXA-181. The Tn 5403 transposon has been previously found in bla NDM– 1 -positive IncN2 plasmids, like plasmid pJN24NDM1 characterized from a ST405 E. coli from China ( Hao et al, 2019 ). On the other hand, plasmid p50595_OXA-181 was almost identical to plasmids p1-Ec-BERN-042 (100% coverage, 99.99% identity; GenBank accession no.…”
Section: Resultsmentioning
confidence: 99%
“…35 IncN2 plasmids were reported in E. coli from human hosts and carried bla NDM-1 gene in Thailand, 36 Australia, 37 and China. 38 IncX1 plasmid was present in two isolates, both are ESBL-producing non-ST131 isolates. IncX1 encoding qnrS1 gene was identified in a previous study in a quinolone-resistant E. coli isolate from animal source.…”
Section: Discussionmentioning
confidence: 98%